Health related quality of life of immigrant children: towards a new pattern in Germany? - Villalonga-Olives, Ester (BMC Public Health, 2014)
BACKGROUND: To study Health related quality of life (HRQoL) of a sample of kindergarten children with migration background. METHODS: Five kindergartens in Frankfurt/Main and Darmstadt (Germany) participated. HRQoL was measured with the Kiddy-KINDL (KK) in 3 to 5 year old children. We examined the associations of HRQoL with socio-demographic variables, positive development and resilience, socio-emotional and motor development. Linear regression models were applied to examine differences in HRQoL between migrant and native-born German children. RESULTS: The response rate was 90.5% (N = 283). The children had predominantly migrant background (81.35%). Perceived health was slightly higher in migrants (69.85, SD 17.00) compared to native-born German children (68.33, SD 17.31, p > 0.05), even though migrant children were characterized by a lower socio-economic status (p < 0.01). CONCLUSIONS: Results suggest that HRQoL at early ages in our study exhibits a different pattern than reported previously in studies among older individuals. We attribute the discrepancy partly to a possible changing pattern of migration in Europe with more migrants capable to migrate with healthy profiles, and to the age of our population. Our findings underscore the need to study the life course trajectory of HRQoL among young immigrants and replication in representative samples.